PENGEMBANGAN INSTRUMEN TRYOUT PPG BERBASIS HIGHER ORDER THINKING SKILLS DAN PEDAGOGICAL CONTENT KNOWLEDGE UNTUK GURU IPS - Neni Wahyuningtyas; Fatiya Rosyida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
21st century education requires professional teachers who are able to foster 6C skills, while Indonesia's PISA 2022 achievements are still low. This study aims to develop a tryout instrument for students of Teacher Professional Education (PPG) in the field of social studies at Malang State University to improve their readiness for the Computer-Based Written Test (UTBK). The method used was Research and Development (R&D) with a 4D model. The instrument consisted of 35 questions based on Higher Order Thinking Skills (HOTS) and Pedagogical Content Knowledge (PCK), which were validated by experts, revised, and tested on 950 students. The results showed that 82.86% of the questions were valid, with 100% reliability, good to very good discrimination, a balanced level of difficulty (40% easy, 42.86% medium, 17.14% difficult), and a distractor effectiveness of 63.44%. These findings confirm that the tryout questions are suitable for use as an adaptive assessment instrument to measure the professional competence of social studies teachers.